The swing! : lose the fat and get fit with this revolutionary kettlebell program - Reifkind, Tracy (HarperOne, 2012)
"Tracy Reifkind is bringing this powerful workout--popular among elite athletes, but simple enough for a fitness novice--to its widest audience yet. Her program focuses on the simplest of the kettlebell movements, the swing, to create a fast, accessible workout that makes the body leaner and more muscular body at the same time. As it swings, the kettlebell creates force that demands full-body involvement and constantly engages the core--all with very little impact on the joints. There's no safer, or more effective, way to work the entire body. "--